Implications of diets supplemented with modified bird-eye pepper powder on proximate composition, sensory profile and shelf stability of meat of broiler chickens - Adeola Adegoke; Deborah Balogun; Kayode Filani (Discover Food)
Abstract This study investigated the implications of varying quantities and sieve sizes of bird-eye pepper (BeP) on proximate composition, sensory profile and shelf stability of meat of broiler chickens. Post-feeding 246 birds BeP-incorporated diets [quantity (0, 150 and 300 g), sieve size (0.05 and 0.1 mm)] randomized to six treatments replicated 4 times in a 3 × 2 factorial arrangements, forty-eight chickens (two per replicate) were slaughtered and muscles extracted. Data for proximate composition and shelf stability with p-value < 0.05 was considered significant, while sensory profile was descriptively illustrated. Pepper (quantity: sieve size) addition increased (p < 0.05) meat ether extract (300 g; 0.05 mm) and moisture (150 g; 0.10 mm) content, while 150 g (0.05 mm) and 300 (0.1 mm) BeP diets increased (p < 0.05) meat ether extract. Dietary 0.1 mm BeP enhanced meat sensory profile, excluding colour and tenderness (0.05 mm BeP diet). Diet of 300 g (0.1 mm) BeP yielded highest flavour, juiciness, hotness, overall flavour and acceptability values, whereas diets of 150 g (0.05 mm) and 300 g (0.05 mm) BeP yielded peak colour and tenderness scores respectively. Dietary 150 g (0.10 mm) BeP resulted in low (p < 0.05) meat pH (0 h) compared to both control groups, while meat of birds fed diet of 150 g BeP stored for 3 days had lowered (p < 0.05) malondialdehyde content. Dietary 300 g (0.1 mm) BeP is desirable for an enhanced profile of meat, however, external antioxidants should be added prior to enhance its shelf stability.